Faculty development programmes: Essential for empowering health professional educators to blend AI in medical education - Rabia Aftab; Shaur Sarfaraz; Azam Afzal (Journal of the Pakistan Medical Association, 2025)
Artificial Intelligence is an area of computer science thatemphasizes the use of machine learning algorithms tomimic human thinking and problem-solving. The fastexpansion of AI in today’s world can be credited to theprogress of algorithms, reasonable graphic processorsand expanded annotated databases.1 AI is an essential tool in addressing complex healthcareissues worldwide. However, AI acceptance andintegration in medical education took time, andsignificant advancements and broader adoption becamemore prominent after 1980s. Also, the application of AI inmedical education has grown significantly over the past20 years, as shown by the rising volume of publications inthis area. Given the widespread use of AI in many facets ofmedical practice, educational programmes pertinent tothis field have to be created and put into place inacademic institutions.2 Continued...